Cementum, apical morphology and hypercementosis: a probable adaptive response of the periodontal support tissues and potential orthodontic implications - Alberto Consolaro; Renata B. Consolaro; Leda A. Francischone (Dental Press Editora, 2012)
Information about orthodontic movement of teeth with hypercementosis is scarce. As cementum deposition continues to occur, cementum is expected to change the shape of the root and apex over time, but this has not yet been demonstrated. Nor has it ever been established whether it increases or decreases the prevalence of root resorption during orthodontic treatment. The unique biological function of the interconnected network of cementocytes may play a role in orthodontic movement and its associated root resorptions, but no research has ever been conducted on the topic. Unlike cementum thickness and hypercementosis, root and apex shape has not yet been related to patient age. A study of the precise difference between increased cementum thickness and hypercementosis is warranted. Hypercementosis refers to excessive cementum formation above and beyond the extent necessary to fulfill its normal functions, resulting in abnormal thickening with macroscopic changes in the tooth root, which may require the delivery of forces that are different from conventional mechanics in their intensity, direction and distribution. What are the unique features and specificities involved in moving teeth that present with hypercementosis? Bodily movements would be expected to occur, since inclination might prove difficult to achieve, but would the root resorption index be higher or lower?